Pengembangan Kurikulum Berorientasi Pada Mutu Pendidikan - Zainudin Zainudin (Jurnal Al-Amin: Kajian Pendidikan dan Sosial Kemasyarakatan, 2021)
The curriculum is a tool to achieve educational goals, namely improving the quality of Indonesian people, namely humans who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens.Etymologically the word curriculum is taken from the Greek, Curere means the distance that must be traveled by runners from start to finish. While in terminology, there are differences in the meaning of curriculum. In the old sense, the curriculum is defined as a number of subject matter that must be taken and studied by students to acquire a certain amount of knowledge, which has been arranged systematically and logically.The notion of development refers to an activity that produces a "new" method, where during the activity, evaluation and improvement of the method continue to be carried out. This understanding of development also applies to the educational curriculum. Because curriculum development is also related to the preparation of the curriculum itself and its implementation in educational units accompanied by intensive evaluation. Murrary Print said that curriculum development is "curriculum development is defined as the process of planning, constructing, implementing and evaluating learning opportunities intended to produce desired changes in learner's". It means that curriculum development is, as a process of planning, building, implementing, and evaluating learning opportunities that are expected to produce changes in learning.These components are, objectives, program or material, process and evaluation. In summary, Majid suggests three functions of the curriculum, focusing on three aspects: first, for the school concerned, the curriculum serves as a tool to achieve a set of desired educational goals and as a guide in regulating daily learning activities. Second, for the school level, namely as the custodian of the education process and preparation of the workforce. Third, for consumers, the curriculum functions as participation in facilitating the implementation of educational programs and constructive criticism in improving the harmonious program.